BELGI BILDIRUVCHI SO‘ZLARNING METAFORA HOSIL QILISHDAGI O‘RNI (Shavkat Rahmon ijodi misolida) - Yunusova, D. (ILIM hám JÁMIYET, 2020)
The article analyzes the role of qualitative words in the formation of metaphors. Also, the ways of formation of metaphors expressing the sign, the possibilities of effective use of language tools were studied, in the works of Shavkat Rahmon.